KEBIJAKAN EUROPEAN UNION DALAM MENANGANI PENGHINDARAN PAJAK MELALUI CRYPTOCURRENCY - Damayanti, Shinta; Ananda, Budi Cahya; Ardi, Andre (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to analyze the European Union's policy response to increasingly sophisticated tax avoidance practices facilitated by the rise of cryptocurrency between 2013 and 2023. It adopts a qualitative research method with a descriptive approach and draws upon literature studies of books, scholarly journals, policy reports, and official online sources. The phenomenon of digital globalization and the growing adoption of cryptocurrency as an alternative asset have posed critical challenges to the integrity of transnational taxation systems, particularly within the EU. This research employs concepts of regionalism, regional organizations, and tax avoidance theory related to crypto assets to evaluate the effectiveness of the EU’s policy instruments. Findings indicate that the European Union has progressively developed a regional policy framework, including anti-money laundering regulations on crypto transactions, enhanced roles for central authorities in overseeing digital assets, and more integrated cross-border information exchange mechanisms. These measures aim to limit the maneuvering space of tax avoiders, strengthen fiscal transparency, and reinforce the institutional legitimacy of regional governance in the face of digital economic transformations. The study contributes to the broader understanding of how regional organizations adapt to evolving economic realities and the shifting architecture of global taxation.